2019
DOI: 10.3390/ijms20225750
|View full text |Cite
|
Sign up to set email alerts
|

Associations of MicroRNAs, Angiogenesis-Regulating Factors and CFH Y402H Polymorphism—An Attempt to Search for Systemic Biomarkers in Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) remains the leading cause of blindness in elderly people, but the pathophysiology of this disease is still largely unknown. We investigated the systemic expression of angiogenesis-regulating growth factors and selected miRNAs known to regulate angiogenesis in AMD patients. We also focused on possible correlations of their expression with the presence of CFH Y402H or ARMS A69S risk variants. A total of 354 AMD patients and 121 controls were enrolled in this study. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 77 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…Accumulating studies have suggested that a number of miRNAs are abnormally expressed and stably exist in the blood or its cellular components (e.g., peripheral blood mononuclear cells (PBMCs)), making them ideal circulating biomarkers for early detection in different clinical states. Indeed, our previous analysis of miRNA expression profiling in vascular disorders, including retinal neovascularization, showed a close correlation with clinical symptoms, suggesting that biological activity of circulating PBMCs may reflect the actual state of microvasculature [27,28]. The role of miRNAs has been also reported in the context of neonatal diagnostics and the first description of miRNA profiling in UCB was reported in 2015 [29].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Accumulating studies have suggested that a number of miRNAs are abnormally expressed and stably exist in the blood or its cellular components (e.g., peripheral blood mononuclear cells (PBMCs)), making them ideal circulating biomarkers for early detection in different clinical states. Indeed, our previous analysis of miRNA expression profiling in vascular disorders, including retinal neovascularization, showed a close correlation with clinical symptoms, suggesting that biological activity of circulating PBMCs may reflect the actual state of microvasculature [27,28]. The role of miRNAs has been also reported in the context of neonatal diagnostics and the first description of miRNA profiling in UCB was reported in 2015 [29].…”
Section: Introductionmentioning
confidence: 84%
“…What is more, down-regulation of several "Angio-miRs" could be observed in different types of vascular disorders in adult patients. For example, our recent analyses showed that in the blood of patients with age-related retinal degeneration, which is characterized by abnormal vascularization and subsequent macular dysfunction, several significantly down-regulated miRNAs were detected, such as miR-17, miR-21-3p, miR-150, and miR-155, and they were associated with lower blood levels of FGF-basic molecule with potential angiogenesis-regulating function [27,28]. Similar results were obtained from computational analysis of miRNA expression in UCB from prematurely-born infants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…AMD remains the major cause of visual impairment among the elderly population, significantly reducing the quality of life of affected individuals [ 40 ]. Several genetic and environmental factors, including the CFH Y402H polymorphism, age and cigarette smoking, have been identified as contributing to the complex landscape of AMD, although the exact pathogenesis of the disease remains unclear [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In total, six studies met these criteria [21][22][23][24][25][26]. Studies that investigated intracellular cmiRNAs [54,55], cmiRNAs in exosomes [56], a combination of nAMD and geographic atrophy AMD patients [57,58], and a combination of nAMD and congenital hemochromatosis patients [59] were excluded.…”
Section: Literture Analysis Of Differentially Expressed Cmirnas In Namentioning
confidence: 99%